Всеобъемлющий : Studium jednego przypadku - Białek, Ewa (Acta Neophilologica, 2019)
This article comprises the results of research with respect to diplomacy and foreign policy vocabulary from the lexicographic, comparative and translational perspectives. The equivalents of the adjective всеобъемлющий proposed as new solutions are based on the analysis of its occurrences in word combinations found in contemporary texts. Importantly, it is proven that Polish bilingual dictionaries focus on a narrow aspect of the semantics of this adjective. This conclusion is also supported by the survey of Russian monolingual dictionaries, the analysis of the potential of its English counter- part comprehensive as well as data found in IATE multilingual terminological database.